Oxford Handbook of Medical Sciences, 1st Edition - Wilkins, Robert, Cross, Simon; Megson, Ian; Meredith, David (OXFORD UNIVERSITY PRESS, 2006)
This Handbook is written by Biomedical Scientists and Clinicians to disseminate the fundamental scientific principles that underpin clinical medicine. Frequent cross-referencing with the Oxford Handbook of Clinical Medicine helps to highlight the clinical relevance of specific issues. The challenge of this ambitious undertaking was to distil the contents of information found in several voluminous textbooks into a conveniently-sized handbook, without loss of important information. This has been achieved by sifting out the key facts that are crucial to understanding fundamental principles and presenting them as clear, brief statements or straightforward diagrams. The Handbook has been deliberately divided into sections that mirror modern medical teaching strategies; it builds from a clear, easily digestible account of basic cell physiology and biochemistry to an investigation of the traditional piers of medicine (anatomy, physiology, biochemistry, pathology, and pharmacology), intertwined in the context of each of the major systems relevant to the human body. Although primarily aimed at medical students, this Handbook will also provide a useful reference for science students studying any of the traditional biomedical sciences.